Postpartum Depression in American Indian/Alaska Native Women: A Scoping Review. Issue 1 (January 2021) - Heck, Jennifer L.
Abstract: Background: Postpartum depression (PPD) is the most common complication of childbirth and affects one in nine new mothers in the United States. Objective: The purpose of this review was to synthesize PPD research in American Indian/Alaska Native (AI/AN) women. Specific aims were to 1) explore the extent to which PPD literature includes AI/AN women measured by the proportion of study samples that were AI/AN women and 2) identify and analyze gaps in the PPD literature for AI/AN women. Design: Databases were searched using: "postpartum depression" and "American Indian, " "Native American, " "Alaska Native, " "Inuit, " and "Indigenous." "Postpartum depressive symptoms" and "puerperal mood disorder" were each paired with race/ethnicity search terms, yielding a final sample of nine articles. Results: The proportion of study samples that were AI/AN women ranged from 0.8% to 100%. Compared with all women in the United States (11%), AI/AN women have higher PPD prevalence (14%-29.7%), suggesting a disparity among the different groups of women. Screening instruments were inconsistent among studies, and not all studies used a screening instrument specific to PPD. No cultural influences, risk, or protective factors were reported for AI/AN women. In the only intervention study, no significant differences in PPD symptoms between groups were found after the intervention. Conclusions: This review uncovered significant gaps in the literature and suggested ways to advance the PPD science for AI/AN women. Clinical implications were described. Abstract : American Indian, Native Alaskan, and Indigenous women are not well represented in the postpartum depression literature. In this review, gaps in the literature are identified and suggestions for future research are offered.